2010
DOI: 10.1002/mnfr.200900609
|View full text |Cite
|
Sign up to set email alerts
|

Diosgenin present in fenugreek improves glucose metabolism by promoting adipocyte differentiation and inhibiting inflammation in adipose tissues

Abstract: In obesity, adipocyte hypertrophy and chronic inflammation in adipose tissues cause insulin resistance and type-2 diabetes. Trigonella foenum-graecum (fenugreek) can ameliorate hyperglycemia and diabetes. However, the effects of fenugreek on adipocyte size and inflammation in adipose tissues have not been demonstrated. In this study, we determined the effects of fenugreek on adipocyte size and inflammation in adipose tissues in diabetic obese KK-Ay mice, and identified the active substance in fenugreek. Treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
76
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 129 publications
(86 citation statements)
references
References 55 publications
6
76
0
Order By: Relevance
“…On the other hand, several studies have shown that T. foenum-graecum has antioxidative, anti-inflammatory, and immunomodulatory activities in male and female animals (16)(17)(18)(19). For example, it was demonstrated that diosgenin induces anti-inflammatory action in adipose tissue (36). Sindhu et al reported that EE of T. foenum graecum decreases the blood levels of IL-1, IL-2, IL-6, and TNF-α in female rat model of arthritis (19) Also, treatment with hydroalcoholic extract of T. foenum graecum seed reduces oxidative stress and the proinflammatory cytokines TNF-α and IL-6 in diabetic rats (37).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, several studies have shown that T. foenum-graecum has antioxidative, anti-inflammatory, and immunomodulatory activities in male and female animals (16)(17)(18)(19). For example, it was demonstrated that diosgenin induces anti-inflammatory action in adipose tissue (36). Sindhu et al reported that EE of T. foenum graecum decreases the blood levels of IL-1, IL-2, IL-6, and TNF-α in female rat model of arthritis (19) Also, treatment with hydroalcoholic extract of T. foenum graecum seed reduces oxidative stress and the proinflammatory cytokines TNF-α and IL-6 in diabetic rats (37).…”
Section: Discussionmentioning
confidence: 99%
“…The enzyme was deactivated by heating at 90˚C. The paste was freeze dried and crushed into powder (10).…”
Section: Methodsmentioning
confidence: 99%
“…1) yields fenugreek with reduced bitterness (FRB). Recently, Uemura et al reported that oral administration of FRB had an antidiabetic effect on obese diabetic KK-Ay mice (10). They suggested that diosgenin (DG) (Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Fenugreek demonstrated beneficial effects on blood glucose and insulin levels, antioxidant enzymes, lipid peroxidation, pyruvate kinase, lactate dehydrogenase, and protein kinase C in the heart, muscle, and brain of the alloxan-induced diabetic rats. Results of the study by Uemura et al [57] showed that T. foenumgraecum can ameliorate hyperglycemia and diabetes. Authors determined the effects of Fenugreek on adipocyte size and inflammation in adipose tissues in diabetic obese KK-Ay mice, and identified the active substance in Fenugreek.…”
Section: Reliable Obesity Animal Modelsmentioning
confidence: 99%